The twelve burps of Christmas - Krulik, Nancy E.; Blecha, Aaron (New York : Grosset & Dunlap, 2012)
In two separate stories, George looks forward to Christmas but the class play and and a surprise visit with Kevin, his best friend from when he lived in Cherrydale, are both marred by the magic burps.
Don't be such a flake -- What's a few burps between friends?.
Keywords: Human behavior -- Juvenile fiction; Belching -- Juvenile fiction; Christmas stories; Theater -- Juvenile fiction; Friendship -- Juvenile fiction; Magic -- Juvenile fiction